2017
DOI: 10.1038/s41593-017-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the RNA binding protein TIA1 protects against tau-mediated neurodegeneration in vivo

Abstract: SUMMARY Emerging studies suggest a role for tau in regulating the biology of RNA binding proteins (RBPs). We now show that reducing the RBP T-cell intracellular antigen 1 (TIA1) in vivo protects against neurodegeneration and prolongs survival in transgenic P301S tau mice. Biochemical fractionation shows co-enrichment and co-localization of tau oligomers and RBPs in transgenic P301S tau mice. Reducing TIA1 decreases the number and size of granules co-localizing with stress granule markers. Decreasing TIA1 also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
255
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 207 publications
(272 citation statements)
references
References 47 publications
14
255
3
Order By: Relevance
“…The results mirror past studies that found opposing effects on ribosomal gene transcript and protein levels in brain samples from patients with tauopathies [17, 28]. Moreover, these findings are not surprising considering the recruitment of tau–ribosome complexes in stress granules with TIA1 [7, 59] Based on our microarray analysis, we also isolated a pronounced doxycycline effect (Fig. 4f).…”
Section: Discussionsupporting
confidence: 90%
“…The results mirror past studies that found opposing effects on ribosomal gene transcript and protein levels in brain samples from patients with tauopathies [17, 28]. Moreover, these findings are not surprising considering the recruitment of tau–ribosome complexes in stress granules with TIA1 [7, 59] Based on our microarray analysis, we also isolated a pronounced doxycycline effect (Fig. 4f).…”
Section: Discussionsupporting
confidence: 90%
“…Compellingly, KD of Ataxin-2 in an ALS mouse model reduced the number of TDP-43 aggregates in the spinal cord of the affected mice and dramatically extended survival [133]. Similarly, KD of SG protein Tia-1, which is known to interact with Tau, was also shown to prevent Tau pathology and toxicity in neuronal culture and rodent models [134,135]. These observations convincingly demonstrate that targeting phase transitions through ASO technology could be a viable strategy to halt pathological aggregation in TDP-43 and Tau proteinopathies, and possibly in other protein aggregation diseases.…”
Section: Road Toward Novel Therapy?mentioning
confidence: 99%
“…Our data also strongly support a role for mRNA splicing and transport in AD pathogenesis (RNA splicing, FDR = 4.48e-10; RNA transport, FDR = 3.32e-16). RNA binding proteins in these processes have recently emerged as major players in various non-AD neurodegenerative diseases 49 , and recent studies suggested possible involvement in AD (TIA1 protects against tau-mediated degeneration 50 , CELF1 is one of the main GWAS hits 51 , and the activity of ELAVL proteins is altered in AD brains 52 ).…”
Section: Identifying Ad-associated Genes Through Integration Of Ad Gwmentioning
confidence: 99%